2008
DOI: 10.1182/blood-2007-09-112631
|View full text |Cite
|
Sign up to set email alerts
|

Expression of spliced oncogenic Ikaros isoforms in Philadelphia-positive acute lymphoblastic leukemia patients treated with tyrosine kinase inhibitors: implications for a new mechanism of resistance

Abstract: Ikaros plays an important role in the control of differentiation and proliferation of all lymphoid lineages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 34 publications
(46 reference statements)
8
83
0
2
Order By: Relevance
“…In human leukemia patients, several reports have shown mutations in the IK gene [95][96][97][98] . More recently, it has been revealed that alternative splicing dysregulation alters the ratio between IK DNA binding to non-DNA binding isoforms [99] .…”
Section: Dorsam Gp Et Al Vip In Human Leukemiamentioning
confidence: 99%
“…In human leukemia patients, several reports have shown mutations in the IK gene [95][96][97][98] . More recently, it has been revealed that alternative splicing dysregulation alters the ratio between IK DNA binding to non-DNA binding isoforms [99] .…”
Section: Dorsam Gp Et Al Vip In Human Leukemiamentioning
confidence: 99%
“…[32][33][34][35][36][37] Expression of aberrant IKAROS isoforms in ALL blasts had been recognized for many years, particularly one isoform, IK6, which lacks the N-terminal zinc fingers of IKAROS and cannot bind DNA, but retains the C-terminal zinc fingers and can act in a dominant-negative manner. [38][39][40] Before detailed DNA copy number analyses of ALL, the factors determining expression of these aberrant IKZF1 isoforms had been unclear, and post-transcriptional mechanisms induced by BCR-ABL1 had been suggested. 40,41 However, single-nucleotide polymorphism array profiling studies of both ALL and chronic myeloid leukemia have shown that expression of these dominant-negative transcripts is determined by the presence of IKZF1 deletions that involve the exons corresponding to those deleted in the aberrant IKZF1 transcripts and IKZF1 protein.…”
Section: Genomic Profiling Of High-risk Allfa Central Role Of Ikzf1mentioning
confidence: 99%
“…[38][39][40] Before detailed DNA copy number analyses of ALL, the factors determining expression of these aberrant IKZF1 isoforms had been unclear, and post-transcriptional mechanisms induced by BCR-ABL1 had been suggested. 40,41 However, single-nucleotide polymorphism array profiling studies of both ALL and chronic myeloid leukemia have shown that expression of these dominant-negative transcripts is determined by the presence of IKZF1 deletions that involve the exons corresponding to those deleted in the aberrant IKZF1 transcripts and IKZF1 protein. 20,30 Alterations in IKAROS function have an important role in the pathogenesis of lymphoid tumors.…”
Section: Genomic Profiling Of High-risk Allfa Central Role Of Ikzf1mentioning
confidence: 99%
“…IKZF1 encodes a critical tumour suppressor which is frequently mutated in pre-B ALL (Mullighan 2011), and these mutations typically result in synthesis of dominant negative (DN) forms that dimerise with canonical IKZF1. Additionally however, these DN forms can arise by alternative splicing in the absence of mutation (Iacobucci, Lonetti et al 2008;Capece, Zazzeroni et al 2013). …”
Section: Discussionmentioning
confidence: 99%